α-Glucosidase inhibitory activity of selected Malaysian plants - Mohd Bukhari, Dzatil Awanis; Siddiqui, Mohammad Jamshed Ahmad; Shamsudin, Siti Hadijah; Rahman, Md. Mokhlesur; Mat So'ad, Siti Zaiton (Wolters Kluwer, 2017)
Diabetes is a common metabolic disease indicated by unusually high plasma glucose level that can lead to major complications such as diabetic neuropathy, retinopathy, and cardiovascular diseases. One of the effective therapeutic managements of the disease is to reduce postprandial hyperglycemia through inhibition of α-glucosidase, a carbohydratehydrolyzing enzyme to retard overall glucose absorption. In recent years, a plenty of research works have been conducted looking for novel and effective α-glucosidase inhibitors (AGIs) from natural sources as alternatives for the synthetic AGI due to their unpleasant side effects. Plants and herbs are rich with secondary metabolites that have massive pharmaceutical potential. Besides, studies showed that phytochemicals such as flavonoids, alkaloids, terpenoids, anthocyanins, glycosides, and phenolic compounds possess significant inhibitory activity against α-glucosidase enzyme. Malaysia is a tropical country that is rich with medicinal herbs. In this review, we focus on eight Malaysian plants with the potential as AGI to develop a potential functional food or lead compounds against diabetes.